'You Want to Get it Right': A Regional Queensland School's Experience in Strengthening Parent–school Partnerships. Issue 3 (September 2016) - Campbell, Claire; Dalley-Trim, Leanne; Cordukes, Lorraine
THIS PAPER DISCUSSES THE key findings from a qualitative case study that was conducted in response to one regional Queensland state school's identified need for a customised approach to parent engagement in the early years. Data was collected via six semi-structured focus group interviews with parents ( n = 18) of children in the Preparatory year level at the school. A priori analysis of the data revealed three key barriers to parents' engagement with the school: communication, consistency and family commitments. The intention of this study was to capture parents' perspectives and experiences in order to customise and strengthen the school's approach to parent engagement. The key findings and implications presented herein contribute to the body of knowledge on parent engagement practices in early childhood education settings. Moreover, this article emphasises the importance of the development of an individualised approach to parent engagement that is informed by parents.